Kepentingan Nasional Amerika Serikat Dalam Drugs and Peace Agreement Colombia 2016 - Wicaksono, Arief; H Nurlette, Wahyu Triazaldhi (Journal of International and Local Studies, 2021)
This article describes the United States' national interests behind the Colombia 2016 Drugs and Peace Agreement. I assume, the peace agreement between the left-wing guerrilla group Fuerzas Armadas Revolucinarias De Colombia (FARC) and the Colombian Government which is fighting over territory of influence in the narcotics and drug abuse industry in Colombia, is very thick with the interests of the United States in the War on Drugs agenda. For this reason, the author uses qualitative research methods with library research data collection techniques, by focusing research on influential actors. By using two of the four indicators of national interest according to Nuechterlein, namely economic interests and defense interests, the author finds an illustration that to pursue economic interests, the United States opens the tap of bilateral relations with Colombia through export and import activities as well as investment. Meanwhile, in the interests of defense, the United States provides military assistance in helping Colombia to monitor and overcome the problem of coca cultivation and also conducts special training to the Colombian military.